Establishment of propagation methods for growing promisingaromatic plant species of the lippia (verbenaceae) andtagetes (asteraceae) genera in colombia (2013)
The objective of this study was to evaluate methods of asexual propagation with stem cuttings in the aromatic plant species Lippia origanoides (accessions CA-90 and CA-93), Lippia alba (accession CA-300) and Tagetes zypaquirensis (accession CA-247) and determine the germination behavior of Tagetes caracasana (accession CA-10), in order to contribute to the establishment of these promising aromatics as potential new crops in Colombia. The factors evaluated were the substrate (fine coconut fiber (FCF); fine coconut fiber: coal slag 1:1 (FCFCS); fine coconut fiber: coal slag: river sand 1:1:1 (FCFC- SRS) and IBA hormone concentration (0, 2,000 and 4,000 mg L-1). Germination tests of seeds of the accession CA-10 were carried out in Petri dishes with 50 seeds per dish, with three replicates in controlled conditions and constant temperature (25oC), humidity (90%) and total darkness. In general, the accessions CA-90, CA-93, CA-300 and CA-247 showed better rooting percentage, root length, number of roots and root dry weight in the fine coconut fiber substrate and a higher number of roots with an exogenous application of 2,000 mg L-1 IBA. L. alba and T. zypaquirensis responded better than L. origanoides to the treatments. The latter species showed a relatively poor performance and may require more complex and improved propagation methods to obtain more satisfactor y results. T. caracasana seeds had a relatively short germination time (less than three weeks) and relatively high germination under controlled laboratory and greenhouse conditions (70 and 60%, respectively); these percentages are high relative to wild species of the same genus, meaning this method of seed propagation is appropriate for this wild species.